The relationship between anger and suicidal ideation: Investigations in two samples. Issue 9 (23rd February 2022) - Schafer, Katherine Musacchio; Daurio, Allison; French, Juliana E.; Rogers, Megan L.; Meltzer, Andrea L.; Cougle, Jesse R.; Joiner, Thomas E.
Abstract: Objectives: Suicidal ideation (SI) nearly always precedes lethal suicide attempts. Anger may play a role in SI, but this appears to vary by gender and nuances in this relationship are unclear. Method: We investigated whether levels of (a) anger and (b) SI vary by gender, (c) the cross‐sectional relationship between anger and SI, and (d) if gender moderates that relationship in two samples: adults seeking care for excessive anger (Study 1) and undergraduates endorsing previous suicide attempt (Study 2). Results: In Study 1, anger was more commonly endorsed in women; however, in Study 2, anger did not vary by gender. In both studies, SI did not vary by gender. Further, in both studies, anger and SI were positively related. The relationship between anger and SI did not vary by gender in either study. Conclusions: The strength of the relationship between anger and SI did not vary by gender.